Innovation platforms and institutional change: the case of small-scale palm oil processing in Ghana - Adjei-Nsiah, Samuel; Klerkx, Laurens (EDP Sciences, 2016)
Oil palm is an important industrial, livelihood and food crop in Ghana. Smallholders produce the bulk of the palm fruits and small-scale processors, mainly women, produce most of the crude palm oil. Poor practices lead to a high proportion of free fatty acids in the crude palm oil and the processors thus cannot access remunerative national and international markets. Exploratory and diagnostic studies identified the absence of rules and regulations governing processing as a major factor. An innovation platform was convened and facilitated to remove the identified institutional constraints. Based on event tracing, this paper reports a study of the effects of the innovation platform's interventions and how these were achieved. Institutional entrepreneurs are shown to play important roles: they mobilised resources such as expertise, knowledge, access to information and high-level political power to influence small-scale processors to adopt alternative practices. The institutional changes observed are shown to arise in cooperation between traditional authorities (chiefs), the district legislature and authorities at the national level, who together institutionalised the experimental actions and processes taken in the study area. The institutional elements they most affected were: rules and regulations, the legitimacy of new practices and organisational arrangements, co-generation of knowledge, material resources, and the strategic and communication skills of key actors.